Reconfigurable intelligent surfaces: interplay of unit cell and surface-level design and performance under quantifiable benchmarks - Rafique, Ammar (2024)
The ability of reconfigurable intelligent surfaces (RIS) to produce complex radiation patterns in the far-field is determined by various factors, such as the unit cell's design, spatial arrangement, tuning mechanism, the communication and control circuitry's complexity, and the illuminating source's type (point/planewave). Research on RIS has been mainly focused on two areas: first, the optimization and design of unit cells to achieve desired electromagnetic responses within a specific frequency band, and second, exploring the applications of RIS in various settings, including system-level performance analysis. The former does not assume any specific full radiation pattern on the surface level, while the latter does not consider any particular unit cell design. Both approaches largely ignore the complexity and power requirements of the RIS control circuitry. As we progress toward the fabrication and use of RIS in real-world settings, it is becoming increasingly necessary to consider the interplay between the unit cell design, the required surface-level radiation patterns, the control circuit's complexity, and the power requirements concurrently. In this paper, we propose a benchmarking framework comprising a set of simple and complex radiation patterns. Using full-wave simulations, we compare the relative performance of various RISs made from unit cell designs that use PIN diodes as control elements in producing the full radiation patterns in the far-field of the RIS under point/planewave source assumptions. We also analyze the control circuit complexity and power requirements and explore the tradeoffs of various designs.